Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru - Faudi Faudi; Muchsin Muchsin (2021)
Teacher performance is one of the important factors for the implementation of quality education and learning. Efforts to improve performance are influenced by many factors, including the leadership of the principal. The author in this article will explain the description of the principal's leadership in making plans, compiling school organizations, acting as coordinators and directors, and carrying out staffing management. Teacher performance and development, factors that affect teacher performance, factors that can improve performance, teacher performance in the teaching and learning process, human resource development strategies, principals' efforts to foster teacher performance. In its application, teacher performance improvement can be seen from teaching and learning interactions, learning preparation, learning process, evaluation of learning determined by the leadership of the principal.